Characterization of Lactose-Free Dulce de Leche - Olcay Mercan; Zerrin Yüksel (Turkish Journal of Agriculture: Food Science and Technology, 2023)
The aim of the study is to be determine the effect of lactose hydrolysis and sugar content on physicochemical properties, sensory profile and HMF (5-hydroxymethylfurfural) content in Dulce de Leche (DL). Lactose free (lactose-hydrolysed) dairy products as well as low sugar products have been developed to supply consumer demand. Two different sucrose concentrations, 16% and 20%, were used in milk jam samples produced by the traditional method. For the formation of desired colour and flavour in the Dulce de Leche, Maillard reaction products are mainly responsible. HMF is Maillard reaction indicator analysed in this work. Fat, protein, solid content, ash, lactic acid and pH analysis were carried out. Sucrose, glucose, fructose and lactose concentrations were determined. Lightness, yellowness and redness as colour parameters of DL samples were evaluated and sensory analyses were also performed. It has been revealed that lactose hydrolysis causes significant changes in the color parameters and sensory profile of the samples. In this study, less or no HMF was detected in the lactose hydrolyzed DL samples compared to the control samples.